Peran Chatbot GPT dalam Meningkatkan Kompetensi Menulis Kreatif pada Mata Pelajaran Bahasa Indonesia di kelas 12 SMA Mandalahayu Bekasi - Amal, Bahar; Zein, Adika Ananta; Revalina, Adysty; Qothrunada, Faiha; Pratiwi, Naisya Rosy; Larasati, L (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2025)
The study explesses the challenges faced by 12th graders at the mandcity of bekasi in teaching creative writing skills, as well as the potential use of artificial intelligence (ai) technology to enhance the learning process. Surveys indicate that the development of ideas, grammar, and consistency of story lines is a major obstacle students face. On the other hand, the use of ai based tools, such as chatgpt, has been shown to offer constructive feedback, correct mistakes, and provide a quality writing example, thus encouraging students to be more open to the technology of writing. These findings provide insight for educators to effectively integrate technology in creative writing learning